Ministerial Decree No. 150/2010 Regarding the conditions and regulations governing the timeshare system in hotel establishments, tourist villages and resorts = قرار وزاري رقم 150 لسنة 2010 بشأن شروط وضوابط نظام اقتسام الوقت "التايم شير" في المنشآت الفندقية والقرى والمنتجعات السياحسة - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of Tourism decree no. 150 of the year 2010 issued on 8/3/2010 regarding the conditions and regulations governing the timeshare system in hotel establishments, tourist villages and resorts وزارة السياحة قرار رقم 150 لسنة 2010 صادر بتاريخ 8/3/2010 بشأن شروط وضوابط نظام اقتسام الوقت "التايم شير" فى المنشآت الفندقية والقرى والمنتجعات السياحية